Police Misconduct as a Cause of Wrongful Convictions - Russell Covey (Washington University Law Review, 2013)
This study gathers data from two mass exonerations resulting from major police scandals, one involving the Rampart division of the L.A.P.D., and the other occurring in Tulia, Texas. To date, these cases have received little systematic attention by wrongful convictions scholars. Study of these cases, however, reveals important differences among subgroups of wrongful convictions. Whereas eyewitness misidentification, faulty forensic evidence, jailhouse informants, and false confessions have been identified as the main contributing factors leading to many wrongful convictions, the Rampart and Tulia exonerees were wrongfully convicted almost exclusively as a result of police perjury. In addition, unlike other exonerated persons, actually innocent individuals charged as a result of police wrongdoing in Rampart or Tulia only rarely contested their guilt at trial. As is the case in the justice system generally, the great majority pleaded guilty. Accordingly, these cases stand in sharp contrast to the conventional wrongful conviction story. Study of these groups of wrongful convictions sheds new light on the mechanisms that lead to the conviction of actually innocent individuals.
Keywords: Rampart; Tulia; wrongful conviction